2019
DOI: 10.1016/j.jvs.2019.01.089
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results from the Study of Thoracic Aortic Type B Dissection Using Endoluminal Repair (STABLE I) study of endovascular treatment of complicated type B aortic dissection using a composite device design

Abstract: Objective: We report the final 5-year results from the Study of Thoracic Aortic Type B Dissection Using Endoluminal Repair (STABLE I) study, a prospective, single-arm, multicenter study of the Zenith Dissection Endovascular System (William Cook Europe, Aps, Bjaeverskov, Denmark), a pathology-specific device comprising a proximal stent graft with barbs and a distal bare stainless steel stent for the treatment of patients with complicated type B aortic dissection. Methods:The study prospectively enrolled 86 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 20 publications
1
53
1
1
Order By: Relevance
“…68 In the prospective, multicenter STABLE study, 9 a stent-graft combined with a bare stent to treat cATBAD reduced the incidence of 30-day mortality to 5% and 1-year mortality to 10%. Additionally, beneficial aortic remodeling was observed at 2-year 10 and 5-year 11 follow-up. In China, a recent study showed that TEVAR with a distal bare stent reduced complications and improved favorable aortic remodeling by increasing FL thrombosis and preventing TL collapse.…”
Section: Introductionmentioning
confidence: 86%
“…68 In the prospective, multicenter STABLE study, 9 a stent-graft combined with a bare stent to treat cATBAD reduced the incidence of 30-day mortality to 5% and 1-year mortality to 10%. Additionally, beneficial aortic remodeling was observed at 2-year 10 and 5-year 11 follow-up. In China, a recent study showed that TEVAR with a distal bare stent reduced complications and improved favorable aortic remodeling by increasing FL thrombosis and preventing TL collapse.…”
Section: Introductionmentioning
confidence: 86%
“…This strategy provided diffuse mechanical aorto-iliac support and led to complications necessitating re-intervention when treating extensive TBAD. Based on the concept of PETTICOAT, Lombardi JV et al proposed a composite device design to treat complicated type B aortic dissection [ 17 ]. The device comprised a pathology-specific device comprising a proximal stent graft with barbs and a distal bare stainless steel stent.…”
Section: Trans-tl Repairmentioning
confidence: 99%
“…5,7 In contrast, in the Study of Thoracic Aortic Type B Dissection Using Endoluminal Repair (STABLE I), favorable results were found with the Zenith Dissection Endovascular System (Cook Medical) with a 30-day paraplegia rate of 1.8%. 6 Less disruption of spinal cord perfusion with the use of bare metal stent, continued FL compression to encourage thrombosis and remodeling. 9 There is limited data on TEVAR/EVAR for patients with MFS and only a few case reports presented PETTICOAT technique for patients with MFS.…”
Section: Commentsmentioning
confidence: 99%
“…[2][3][4] Use of the provisional extension to induce complete attachment (PETTICOAT) technique has been demonstrated to decrease the risk of spinal cord ischemia in comparison to use of covered stent grafts in similar settings. [5][6][7][8]…”
Section: Introductionmentioning
confidence: 99%